Wars and epidemics in the books of islamic military school: Methods of epidemic spreading and prevention during war as a model - ZITOUNI , Bilel (La Revue d’Histoire Méditerranéenne, 2024)
This paper explores the historical development of military strategies and the theoretical foundations of using epidemics as a tool of warfare to secure victory during conflicts. The examination of this unconventional form of warfare highlights the intellectual and strategic acumen of Arab Muslim theorists and historians, as reflected in their scholarly contributions from later periods. This research scrutinizes various military theories related to the propagation of epidemics in wartime scenarios and the preventive strategies employed, drawing extensively from seminal texts and military categorizations from the Islamic Middle Ages. The study employs a historical-analytical approach to examine the use of epidemics in warfare. It involves a detailed review of primary sources to understand the strategies and theories of the time. Additionally, secondary sources, including modern historical analyses and scholarly articles, are used to interpret and contextualize these findings. This study revealed the use of epidemics in wars and battles during advanced periods and demonstrated through the writings and theories of historians and Arabs the application of this type of warfare, especially those related to the propagation of epidemics through « air » and « water ».